Estimation of cerebrovascular insult frequency in emergency patients at the Clinical Hospital Centre Rijeka - Kragulj, Lara (Medical imaging and radiotherapy journal, 2021)
Purpose: Cerebrovascular stroke is defi ned as a sudden focal neurologic defi cit caused by cerebrovascular disease lasting longer than 24 hours. Cerebrovascular insult (CVI) is divided into ischemic and hemorrhagic. Along with heart disease and malignancies, cerebrovascular disease is the most common cause of mortality and disability in the modern world, attributing to this disease being the leading cause of disability across the globe. Diagnosis and identifi cation of the type of stroke requires imaging examination with computed tomography. A detailed history and imaging usually rule out the impersonation of a stroke. Computed tomography (CT) is one of the fi rst diagnostic modalities used to image the brain to identify the diff erence between ischemic and hemorrhagic stroke. The aim of this retrospective analysis was to estimate the incidence of cerebrovascular insult in patients who underwent CT brain examination in the Clinical Department of Radiology at Clinical Hospital Centre (CHC) Rijeka in the period from January 1, 2020, to December 31, 2020. Materials and methods: During this period, 255 data sets from patients' medical records were anonymously collected. The data search included patients who underwent CT of the brain with a clinical question about CVI. Results: The data analysis at CHC Rijeka showed that the incidence of CVI is slightly higher in the male population. It is commonly diagnosed in the population of 81-90 years. About half of the patients with suspected CVI had normal CT fi ndings. Conclusion: These results could serve as a guideline for targeting groups in preventive healthcare interventions and education.
Keywords: computed tomography; hemoragična možganska kap; hemorrhagic stroke; ischemic stroke; ishemična možganska kap; računalniška tomografija